The Meaning of Madura Batik Patterns in a Review of Visual Communication, Culture, and Religiosity Elements - Triandika, Lulus Sugeng; Arifin, Syamsul; Rachmad, Teguh Hidayatul (Sosial Budaya, 2023)
Cultural acculturation and religiosity strongly influence the creation of Madura Batik. The pattern of batik motifs is interesting to study as a dynamically developing cultural product. There is a process of cultural communication in batik, with motifs as the medium. Even though there are many studies on Madura Batik, it is still rare to study motifs, especially from a visual communication perspective. The study was conducted to find out the meaning of Batik motifs. The exploratory qualitative study method was used with a combination of direct observation and literature review. Research sources come from craftsmen, boutique owners, and Madurese cultural figures. Charles Sanders Peirce's Semiotic Analysis is used to examine the object of research on batik motifs. The results found that there were elements of acculturation in the patterns of batik motifs. The process of acculturation occurred from the Hindu-Buddhist era until the modern era. The Islamic aspect is contained in the pattern of batik motifs with the stylization process.